PRP8 intein in Ajellomycetaceae family pathogens: Sequence analysis, splicing evaluation and homing endonuclease activity - Theodoro, Raquel Cordeiro [UNESP]; Volkmann, Gerrit; Liu, Xiang-Qin; Bagagli, Eduardo [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
Inteins are intervening sequences that are transcribed and translated with flanking host protein sequences and then self-excised by protein splicing. Bi-functional inteins also contain a homing endonuclease responsible for their genetic mobility. The PRP8 intein, the most widespread among fungi, occurs in important pathogens such as Histoplasma capsulatum and Paracoccidioides brasiliensis, from the Ajellomycetaceae family. Herein, we describe the bi-functional PRP8 intein in two other Ajellomycetacean pathogens, Blastomyces dermatitidis and Emmonsia parva. Sequence analysis and experimental evidence suggest that the homing endonuclease from PbrPRP8 is inactive. The splicing activity of the PRP8 intein from the B. dermatitidis, E. parva and P. brasiliensis species complex was demonstrated in a non-native protein context in Escherichia coil. Since the PRP8 intein is located in a functionally essential nuclear protein, it can be considered a promising therapeutic target for anti-fungal drugs, because inhibition of intein splicing should inhibit proliferation of intein-containing pathogens. (C) 2010 Published by Elsevier B.V.
Keywords: Ajellomycetaceae; Intein; PRP8; Splicing; Homing endonuclease